2013
DOI: 10.7857/jsge.2013.18.1.112
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Analytical Techniques for the Determination of Fluorine Contents in Soil and Solid Phase Samples

Abstract: Current status of soil contamination with fluorine and its source were investigated. The basic principles and procedures of various techniques for the analysis of fluorine contents in soil and solid phase samples were summarized in this review. Analysis of fluorine in solid matrices can be achieved by two types of techniques: (i) UV/Vis spectrophotometer or ion selective electrode (ISE) analysis after performing appropriate extraction steps and (ii) direct solid analysis. As the former cases, the standard meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…해 발생될 수 있지만, 암석 내 존재하는 무기염의 풍화 와 용해를 통해 자연적으로 생성되기도 한다 (Na et al, 2010;An et al, 2013). 불소를 함유하고 있는 광물은 수 백 개에 이르는 것으로 알려져 있으며 (Weinstein and Davison, 2004), 대표적인 불소 함유 광물은 형석(CaF 2 ), 인회석(Ca 5 (PO 4 ) 3 F), 빙정석(NA 3 AlF 6 ), 빌리아우마이트 (NaF), 토파즈(Al 2 (SiO 4 )F 2 등이 있다 (Handa, 1975;Hem, 1985;Apambire et al, 1997;Cronin et al, 2000;Saxena and Ahmed, 2003;Weinstein and Davison, 2004;Chae et al, 2007;Edmunds and Smedley, 2013).…”
Section: 연구논문 ("한국의 골재자원 연구 (Ii)" 특별호)unclassified
“…해 발생될 수 있지만, 암석 내 존재하는 무기염의 풍화 와 용해를 통해 자연적으로 생성되기도 한다 (Na et al, 2010;An et al, 2013). 불소를 함유하고 있는 광물은 수 백 개에 이르는 것으로 알려져 있으며 (Weinstein and Davison, 2004), 대표적인 불소 함유 광물은 형석(CaF 2 ), 인회석(Ca 5 (PO 4 ) 3 F), 빙정석(NA 3 AlF 6 ), 빌리아우마이트 (NaF), 토파즈(Al 2 (SiO 4 )F 2 등이 있다 (Handa, 1975;Hem, 1985;Apambire et al, 1997;Cronin et al, 2000;Saxena and Ahmed, 2003;Weinstein and Davison, 2004;Chae et al, 2007;Edmunds and Smedley, 2013).…”
Section: 연구논문 ("한국의 골재자원 연구 (Ii)" 특별호)unclassified
“…Therefore, other alternative procedures must be examined to determine suitable standard procedures for South Korea. For example, a new analytical procedure based on WDXRF was proposed for the determination of the total uorine concentration in soil (Jung, 2007;An et al, 2013). An et al reported that the detection limit of F concentrations in soil via WDXRF decreases from 800 to 120 mg/kg (An et al, 2013).…”
Section: Environmental and Legal Framework In Koreamentioning
confidence: 99%
“…For example, a new analytical procedure based on WDXRF was proposed for the determination of the total uorine concentration in soil (Jung, 2007;An et al, 2013). An et al reported that the detection limit of F concentrations in soil via WDXRF decreases from 800 to 120 mg/kg (An et al, 2013). Adopting the new WDXRF method as one of the standard procedures may help to determine the uorine concentrations in soils and take immediate remediation actions for uorine-contaminated areas.…”
Section: Environmental and Legal Framework In Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine, an element with atomic number 9, has high electronegativity and thus can readily react with other elements, such as Fe, Al, and Ca. Therefore, fluorine mostly exists as compounds in the natural state, and it is difficult to find fluorine in natural settings as a single element [1,2]. Human activities (e.g., fertilizer use, coal use, and aluminum and steel industrial activities) have resulted in the accumulation of fluorine in soil.…”
Section: Introductionmentioning
confidence: 99%